2019
DOI: 10.7717/peerj.7850
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide inequality in access to full text scientific articles: the example of ophthalmology

Abstract: BackgroundThe problem of access to medical information, particularly in low-income countries, has been under discussion for many years. Although a number of developments have occurred in the last decade (e.g., the open access (OA) movement and the website Sci-Hub), everyone agrees that these difficulties still persist very widely, mainly due to the fact that paywalls still limit access to approximately 75% of scholarly documents. In this study, we compare the accessibility of recent full text articles in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…However, accessing free online material is a popular means of accessing literature for both groups. These findings are expected, given the critical role of access in influencing information-seeking behaviour (Connaway et al, 2011) and the prevalence and necessity of informal and alternative routes of access in countries with poor access to literature, such as India (Gaulé, 2009;Boudry et al, 2019). It also reflects a previous study that found openaccess literature to be the most important source of information among conservation practitioners as well as university and non-university researchers in low-middle income countries (Gossa et al, 2015).…”
Section: Information Pathways and Preferencesmentioning
confidence: 58%
“…However, accessing free online material is a popular means of accessing literature for both groups. These findings are expected, given the critical role of access in influencing information-seeking behaviour (Connaway et al, 2011) and the prevalence and necessity of informal and alternative routes of access in countries with poor access to literature, such as India (Gaulé, 2009;Boudry et al, 2019). It also reflects a previous study that found openaccess literature to be the most important source of information among conservation practitioners as well as university and non-university researchers in low-middle income countries (Gossa et al, 2015).…”
Section: Information Pathways and Preferencesmentioning
confidence: 58%
“…However, accessing free online material is a popular means of accessing literature for both groups. These findings are expected, given the critical role of access in influencing information-seeking behaviour ( Connaway, Dickey & Radford, 2011 ) and the prevalence and necessity of informal and alternative routes of access in countries with poor access to literature, such as India ( Gaulé, 2009 ; Boudry et al, 2019 ). It also reflects a previous study that found open-access literature to be the most important source of information among conservation practitioners as well as university and non-university researchers in low-middle income countries ( Gossa, Fisher & Milner-Gulland, 2015 ).…”
Section: Resultsmentioning
confidence: 97%
“…However, accessing free online material is a popular means of accessing literature for both groups. These findings are expected, given the critical role of access in influencing information-seeking behaviour (Connaway et al, 2011) and the prevalence and necessity of informal and alternative routes of access in countries with poor access to literature, such as India (Gaulé, 2009; Boudry et al, 2019). It also reflects a previous study that found open-access literature to be the most important source of information among conservation practitioners as well as university and non-university researchers in low-middle income countries (Gossa et al, 2015).…”
Section: Resultsmentioning
confidence: 97%